Comparative Analysis of Environmental Protection Laws and Their Impact on Sustainable Development in Rwanda - Mukankubana, Diane (International Journal of Law and Policy, 2024)
Purpose: The aim of the study was to analyze comparative analysis of environmental protection laws and their impact on sustainable development in Rwanda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Environmental protection laws play a crucial role in sustainable development, particularly in Rwanda where the balance between economic growth and environmental integrity is pivotal. A comparative analysis reveals that systematic inclusion of environmental impact assessments and strategic environmental assessments are essential for fostering sustainable development. These processes ensure that environmental considerations are integrated into the planning and decision-making stages of development projects, thereby mitigating negative impacts on the environment. Capacity building at various levels, from macro to micro, is recommended to enhance the understanding and implementation of these laws. Unique Contribution to Theory, Practice and Policy: Legal pluralism, policy diffusion & institutional analysis may be used to anchor future studies on comparative analysis of environmental protection laws and their impact on sustainable development in Rwanda. Practitioners can leverage findings from such studies to identify best practices, lessons learned, and areas for improvement in environmental governance. Policymakers should use comparative analysis findings to inform the design, implementation, and evaluation of environmental policies and regulations at local, national, and global levels.